Research Analysis of Self-Directed Learning to Help Adults in Learning: A Systematic Literature Review - Muhamad Yusuf Wijayakusuma; Dadang Yunus Lutfiansyach; Joni Rahmat Pramudia (Didaktika: Jurnal Kependidikan, 2025)
As new learning methods continue to emerge, self-directed learning remains a crucial element in the field of education. This research employs content analysis to explore self-directed learning as a central theme within studies conducted in Indonesia, focusing on publications indexed in the Scopus database from 2019 to 2024. The findings indicate a notable rise in related publications over the past three years, with quantitative research methods being the most commonly applied and students serving as the primary subjects. Key variables closely associated with self-directed learning include online learning, blended learning, motivation, higher education, and self-regulated learning, all showing strong interrelationships. Based on these insights, the researchers suggest several recommendations for future research, such as increasing the variety of research methodologies, broadening the scope of study participants beyond students, and enhancing the number of internationally published studies within the Scopus index.